Iron Removal from Bauxite by Oxalic Acid and Further Al Extraction by High-Pressure Alkali Leaching - Cam, Aslihan; Turan, M. Deniz (Springer, 2023)
Aluminum production from bauxite is achieved with the Bayer process, which is a hydrometallurgical method. However, in the Bayer process, in time, it is possible to encounter problems such as the formation of excessive amounts of red mud in aluminum production, its environmental risks, its requirement of large storage sites, the excessive production of reactants by ores with low silica modulus, and the need for long leaching times in multi-reactor systems. The reason for using alkali leaching instead of acid in this process is to prevent the iron in the ore from going into solution. In this study, metal extraction from bauxite ore was carried out with a two-stage leaching process. At the first stage, bauxite ore was leached under atmospheric conditions with oxalic acid, iron was selectively extracted into the solution, and the refractory aluminum was enriched in the leaching residue. The optimum leaching conditions at the first stage of the leaching procedure were determined as H2C2O4 concentration: 110 g (H2C2O4)/l (water), leaching temperature: 85 degrees C, leaching time: 120 min, liquid-solid ratio: 25:1 ml (solution)/g (bauxite), and stirring speed: 400 rpm. At this stage, the silica modulus (Al2O3/SiO2) was raised from 6.32 to 8.50, and the formation of red mud was eliminated. The second stage of leaching for extracting Al from the leaching residue was carried out in a pressurized reactor system in the presence of NaOH. At this stage, the optimum leaching conditions were determined as 3-5 M (mol/l) NaOH, leaching temperature: 165 degrees C, leaching time 15-60 min, stirring speed: 400 rpm, and liquid-solid ratio: 25 ml (solution)/g (first leach residue). Under these conditions, Al extraction rate of approximately 70% was achieved. [GRAPHICS] .
Keywords: Bauxite; Pressure leaching; Oxalic acid; Aluminum; Bayer process; Selective leaching